Persistent organic pollutants in cork used for production of wine stoppers. - Mazzoleni, V; Dallagiovanna, L; Trevisan, M; Nicelli, M (Chemosphere, 2005)
Owing to the lipophilic character of some components of cork and the long periods in the open air (during growth and barks storage), there is a risk of the cork becoming environmentally polluted. Moreover, cork stoppers are in contact with wines for periods ranging from a few months to several years; so they must maintain high levels of hygiene. The present work aims to investigate the level of PCBs, organochlorine pesticides, and PAHs in cork from different countries, used for the manufacturing of one-piece wine stoppers. Samples of cork were analysed using a multi-residue method. PCBs were not detected in all the samples; only a few samples contained detectable amounts of DDE; phenanthrene and anthracene were found in all the samples and fluoranthene in fewer cases. It was not possible to find a significant correlation between POPs concentration and origin of cork. Globally, the detected amounts are consistent with values found in foods, so the investigated cork show a suitable hygienic quality.
Keywords: Cork; Organochlorine pesticides; PAHs; PCBs